2016
DOI: 10.1039/c5cp02953h
|View full text |Cite
|
Sign up to set email alerts
|

Formation and stability of gas-phase o-benzoquinone from oxidation of ortho-hydroxyphenyl: a combined neutral and distonic radical study

Abstract: Gas-phase product detection studies of o-hydroxyphenyl radical and O2 are reported at 373, 500, and 600 K, at 4 Torr (533.3 Pa), using VUV time-resolved synchrotron photoionisation mass spectrometry. The dominant products are assigned as o-benzoquinone (C6H4O2, m/z 108) and cyclopentadienone (C5H4O, m/z 80). It is concluded that cyclopentadienone forms as a secondary product from prompt decomposition of o-benzoquinone (and dissociative ionization of o-benzoquinone may contribute to the m/z 80 signal at photon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 64 publications
(121 reference statements)
6
29
0
Order By: Relevance
“…Evidence of the presence of benzoquinone in the product spectra was not found. Formation of ortho-benzoquinone was recently studied by the oxidation of orthohydroxyphenyl radicals in a slow-flow tube reactor [31]. Prompt CO elimination via ring opening and cyclisation yields cyclopentadienone (C 5 H 4 O) [31] which is also considered in the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of the presence of benzoquinone in the product spectra was not found. Formation of ortho-benzoquinone was recently studied by the oxidation of orthohydroxyphenyl radicals in a slow-flow tube reactor [31]. Prompt CO elimination via ring opening and cyclisation yields cyclopentadienone (C 5 H 4 O) [31] which is also considered in the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Following this line of enquiry, Schyman et al reported in a computational study that the peroxyl radical would actually be a less efficient at H atom abstraction from deoxyribose than the uracil-5-yl parent. 13 However, following our recent work on orthohydroxylphenyl radicals, which showed characteristic reaction pathways, 14 we posit that the enol form of the uracil-5-yl radical, with an OH group adjacent to the radical at the 5 position, will significantly change the outcome the radical reaction with O 2 . Thus we set out to investigate the gas-phase reaction of protonated uracil-5-yl radical cation, which should be in the enolic form.…”
Section: Introductionmentioning
confidence: 93%
“…More fundamental quantum calculations have been performed mainly for the C2–C4 hydrocarbon oxidation systems. 16 27 All these Waddington mechanism-related studies are summarized in Table S1 of the Supporting Information 1 ; however, there is still a lack of advanced theoretical treatment of the rate coefficient of this reaction class, and few studies have been concerned specifically with the effect of the reactivity of the isomeric molecule structures.…”
Section: Introductionmentioning
confidence: 99%